Grazing of leaf‐associated Cercomonads (Protists: Rhizaria: Cercozoa) structures bacterial community composition and function. (17th July 2017) - Flues, Sebastian; Bass, David; Bonkowski, Michael
Summary: Preferential food selection in protists is well documented, but we still lack basic understanding on how protist predation modifies the taxonomic and functional composition of bacterial communities. We conducted feeding trials using leaf‐associated cercomonad Cercozoa by incubating them on a standardized, diverse bacterial community washed from plant leaves. We used a shotgun metagenomics approach to investigate the taxonomic and functional changes of the bacterial community after five days protist predation on bacteria. Predation‐induced shifts in bacterial community composition could be linked to phenotypic protist traits. Protist reproduction rate, morphological plasticity and cell speed were most important in determining bacterial community composition. Analyses of co‐occurrence patterns showed less complex correlations between bacterial taxa in the protist‐grazed treatments with a higher proportion of positive correlations than in non‐grazed controls, suggesting that predation reduced the influence of strong competitors. Protist predation influenced 14 metabolic core functions including membrane transport from which type VI secretion systems were in particular upregulated. In view of the functional importance of bacterial communities in the phyllosphere and rhizosphere of plants, a more detailed understanding of predator‐prey interactions, changes in microbial composition and function, and subsequent repercussions on plant performance are clearly required.